Inclusion and Mainstreaming: A Journey - Madalina F. Tincu (Asociación Colombiana de Profesores de Ingles, 2017)
For many, the concept of inclusion remains somewhat vague. What does inclusion actually mean? What does it look like? Is it the same as full inclusion or mainstreaming? A general historical synopsis of the development of special education services will be presented, focusing later on the models designed for second or foreign languages. This will be followed by a clarification of terms. The paper concludes with a short discussion of implications for educational practitioners and district policy makers in EFL/ESL settings. Finally, in addition to the list of references cited in the article, a list of other resources is included below for those interested in further investigation.